Functional capacity of elderly and its assessment - Paula Jankowska; Krzysztof Jankowski; Ewa Rudnicka-Drożak (Kazimierz Wielki University, 2018)
Introduction Disability is becoming progressively more common. It is defined as a limitation in the ability to carry out basic functional activities. A functional ability is determined by many convergent factors. The main cause is physical disability, resulting from many highly various diseases. Further, functional capacity of elderly depends on social and financial support, and the environment. Objectives The aim of this study is to present issue of functional capacity of elderly people and its assessment tools. Results Examination of geriatric patient should be complex. If functional capacity is mentioned, physician is expected to assess patient`s chronic diseases, emotional state and social situation. Then, use of validated tools should be performed. These are ADL, IADL, Barthel Index and FIM. Conclusions When taking care of older people, the assessment of functional status is pivotal. Performing such assessment give many possibilities to physician that help improve patient`s quality of life and everyday safety.Use of validated tools facilitates obtaining some objective data about patient general health status and comparison with the results of tests obtained after the lapse of time, thus detecting new problems becomes easier. The most commonly applicated instruments are ADL, IADL, Barthel Index. Even though, these tools are effective in assessment of elderly functional capacity, a full comprehensive geriatric assessment should be performed after implementing them.